2017
DOI: 10.4172/2169-0138.1000147
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin D on the Treatment and Prevention of Essential Hypertension

Abstract: The vast majority of epidemiological studies have consistently shown that vitamin D levels are inversely related to blood pressure (BP) and the incidence of hypertension (HTN). Animal studies from diet-induced or genetic models of vitamin D deficiency suggest that vitamin D deficiency directly causes HTN. Based on basic and clinical studies, modestly increased renin expression in genetic mouse models of vitamin D deficiency is associated with, but not causally linked to vitamin D deficiency-induced HTN. Our me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 109 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…Over the past 20 years, large-scale cross-sectional and cohort analyses, as well as Mendelian randomization and prospective studies, have demonstrated that serum 25[OH]D levels are inversely related to elevated BP, HTN, and adverse cardiovascular events [8]. These findings are supported by the results of studies using genetic and nutrient-depleted VD-deficient animal models that display hypertensive phenotypes [9]. Collectively, the results of these studies suggest that VDD may also contribute to human HTN and that VD supplementation may be effective means for its prevention and treatment.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Over the past 20 years, large-scale cross-sectional and cohort analyses, as well as Mendelian randomization and prospective studies, have demonstrated that serum 25[OH]D levels are inversely related to elevated BP, HTN, and adverse cardiovascular events [8]. These findings are supported by the results of studies using genetic and nutrient-depleted VD-deficient animal models that display hypertensive phenotypes [9]. Collectively, the results of these studies suggest that VDD may also contribute to human HTN and that VD supplementation may be effective means for its prevention and treatment.…”
Section: Introductionmentioning
confidence: 88%
“…This direction was largely based on the theory that VD could suppress basal expression of the endogenous hormone, renin [ 14 ]. Since that time, many lines of evidence have emerged that suggest that a modest increase in renin levels has little to no impact on VDD-associated HTN [ 8 , 9 ].…”
Section: Vd Supplementation Is Ineffective In Reducing Bp In Vd-suffi...mentioning
confidence: 99%
See 1 more Smart Citation